Determination and Assessment of Levels of Gaseous Air Pollutants Emitted at Ajakanga Dumpsite, Ibadan, Nigeria - Falusi, Bamidele Ayodeji; Odedokun, Omobola Ajibike; Abubakar, Adiketu; Bolarinwa, Oladayo Tunde; Agbike, John Egbe (New Ideas Concerning Science and Technology Vol. 4, 2021)
Municipal solid waste dumpsites have been reported to generate different kinds of air pollutants the world over. Deposition of air pollutants, such as CO, H2S, NH3, NOx and SO2 emitted from municipal solid waste on the leaves of plants growing within the vicinity of dumpsites has adverse effects on their morphological, physiological, and biochemical properties. There is a need for regular monitoring of their levels in the atmosphere. In this study, the concentrations of three gaseous air pollutants (SO2, NOx and NH3) emitted from municipal solid waste and the effect of these gaseous air pollutants on the ascorbic acid contents of tissues of Chromolaena odorata collected at Ajakanga dumpsite, Ibadan, Nigeria, were determined using uv/visible spectrophotometry. The ranges of concentrations obtained for SO2, NOx and NH3 were 255.86–503.66 ?g/m3; 246.67–1,155.79 ?g/m3 and 777.51–1,852.48 ?g/m3 respectively in air samples collected at the dumpsite. The results obtained from this study revealed that there was an enhanced gaseous air pollution of the dumpsite’s environment with the three air quality monitoring parameters investigated (i.e. SO2, NOx and NH3). The increasing order of the gaseous air pollutants at the dumpsite is SO2 < NOx < NH3. Enhanced reduction in the ascorbic acid content of C. odorata naturally growing within the vicinity of Ajakanga dumpsite in comparison to the control site Ajakanga dumpsite was observed.